Exploring shippers' motivations to adopt collaborative truck-sharing initiatives. Issue 5 (4th January 2021) - Islam, Samsul; Uddin, Mohammad Jasim; Shi, Yangyan; Sharif, Taimur; Ahmed, Jashim Uddin
Abstract : Purpose: A seaport is an essential part of a supply chain, but many ports experience truck shortages, creating pressure for port authorities from shippers who need more trucks that move cargo. This study explores and ranks the motives for adopting a truck-sharing concept (where shippers share the same truck for delivery) as a mechanism to improve transport capacity. Design/methodology/approach: This study adopts a multi-method approach – both interviews and surveys. Interviews are first conducted with shippers to explore truck-sharing usage motives. Next, quantitative surveys of both shippers and carriers are conducted to rank those motives. Findings: The study identifies five motives (operational efficiency goal, quick transport solution, sustainability policy, convenience-seeking behavior and secure transport process) for truck-sharing, four critical transport attributes (lower charges for freight, distance travelled, full capacity utilization and environmental recognition), four psychological consequences (monetary savings, greater safety, instant availability of trips and clarification of environmental values), and six core values (secure transport process, being careful of money, ease of doing business, sustainability, status in the community and recognition by customers of shippers). Research limitations/implications: The qualitative results will help researchers better understand how usage motives influence shippers' willingness to share a truck for transport needs. The quantitative results are useful for ranking truck-sharing motives by their importance. Practical implications: Based on the findings, managers of carriers can categorize shippers according to their specific needs and thereby customize promotions to attract more shippers. Originality/value: The findings provide the first, exploratory insights into shippers' motives.